Electrocatalysis of Direct Methanol and Ethanol Oxidation in Polymer Electrolyte Fuel Cells. (14th September 2015) - Aricò, Antonino S.; Sebastian, David; Campagna Zignani, Sabrina; Baglio, Vincenzo
Abstract : Carbon-supported bimetallic PtRu and PtSn catalysts characterized by a high degree of alloying and metallic behavior on the surface were investigated for methanol and ethanol electro-oxidation. The variation of the coverage of adsorbed methanolic residues or the change in selectivity, in the case of ethanol electro-oxidation, with temperature were studied. For the ethanol oxidation, anode selectivity towards CO2, acetic acid or acetaldehyde was analysed in relation to both alloy and oxide contents in the catalyst. In parallel, noble metal oxides (IrOx, RuOx) and valve metal oxides (SnOx, and TiOx) were assessed as promoters for these processes. IrOx gave rise to a significant promoting effect both in the case of methanol and ethanol oxidation. Whereas, the electrocatalytic enhancement produced by the valve metal oxides was generally lower than that of IrOx and RuOx. Multifunctional catalysts appeared to provide a valid route to enhance performance and reliability of methanol and ethanol electro-oxidation processes.